2D-DIGE proteomic analysis of blood plasma reveals changes in immune- and stress-associated proteins following hormonal stimulation of carp males. Issue 118 (November 2021) - Dietrich, Mariola A.; Irnazarow, Ilgiz; Adamek, Mikołaj; Jurecka, Patrycja; Teich, Lukas; Rakus, Krzysztof; Kodzik, Natalia; Chadzińska, Magdalena; Steinhagen, Dieter; Ciereszko, Andrzej
Abstract: In carp aquaculture, hormonal manipulation with an analog of GnRH (Ovopel) and carp pituitary extract (CPE), which act at different levels of the hypothalamic-pituitary-gonadal axis, is a routine practice to enhance sperm production. Our recent studies revealed that hormonal stimulation of male carp was associated with changes in the seminal plasma proteome, including blood origin proteins. Here, we explored whether Ovopel and CPE could affect the blood proteome of male carp. Both preparations induced increases in semen volume, total number of sperm, and testosterone level. However, hormonal stimulation did not affect the plasma cortisol and glucose levels. A comparative proteomic analysis of carp blood plasma between the control (PBS) and the hormonally treated males revealed significant changes (>1.2 <−1.2-fold change, P < 0.05) in the abundance of 30 spots (14 up- and 16 downregulated) and 44 spots (28 up- and 16 downregulated) upon CPE and Ovopel treatment, respectively. The most significantly affected pathways were acute phase response signaling, the coagulation system, LXR/RXR and FXR/RXR activation; however, there were different sets of proteins in Ovopel- and CPE-treated males. The majority of differentially abundant proteins were involved in the regulation of the immune defense response, the response to stress, and complement activation. Moreover hormonal stimulation with CPE markedly increased the bactericidal activity of blood and both preparations caused profound changes in gene expression in hematopoietic organs. This work is important in understanding the biological processes behind the protein-based response to hormonal stimulation of sperm production in fish. Highlights: Hormonal stimulation of spermiation affects blood proteome. Different set of blood proteins is affected for carp pituitary extract and Ovopel treatment. Innate immune and stress responses are triggered after hormonal treatment. Carp pituitary extract treatment markedly increases the bactericidal activity of blood. Hormonal manipulation causes profound changes in gene expression in hematopoietic organs.